أدلة فقه الأقليات: الاستحسان أنموذجا - حرب، أحمد حلمي حسن (جامعة الخليل, 2017)
يهدف هذا البحث إلى تناول الإطار التأصيلي لفقه الأقليات ابتداء، ومن ثم تفصيل القول في أحد الأدلة الأصولية الهامة وهو الاستحسان، باعتباره أليق الأدلة بفقه الأقليات؛ لأن الغالب عليهم جانب الخصوصية والاستثناء، وجانب الترخص ورفع الحرج، وذلك ضمن الخطوط العريضة التي تستثيرها مشكلة البحث حول كيفية تفعيل دليل الاستحسان ضمن أدوات الفتوى التي تعالج واقع الأقليات المسلمة، بعيدا عن التعسف والهوى. ولقد اعتمد الباحث في معالجة مشكلة البحث على المنهج الوصفي القائم على التحليل مع الإفادة من المنهجين الاستنباطي والاستقرائي، ضمن خطة تستعرض جملة الأدلة الأصولية لفقه الأقليات وتؤصل له، وتتناول دليل الاستحسان بدراسة أصل حجيته ومأخذه وشروط اعتباره والإطار التنظيمي لتطبيقه. وكان من نتائج هذه الدراسة: أن الاستحسان دليل هام في فقه الأقليات تتحقق فيه شروط المعيارية ضمن إطار تنظيمي يقوم على محاور من: التكاملية والموضوعية والمشروعية والمنهجية، وعلى نحو يظهر معه أثر هذا الدليل في إغناء البحث الفقهي للأقليات، ومراعاة واقعهم، وضمان اطراد قاعدة الشارع في إسعاد العباد.
This research treats, on the one hand, the fundamentalistic framework of Fiqh the minorities, and it investigates, on the other hand, one of the most rational proofs which is Approbation ‘Estihssan’ as one of the prestigious readings of Fiqh the minorities. The latter are mostly known for their privacy and exception, in addition to the feature of licensing and lifting the embarrassment. Therefore, the article highlights the efficiency of referring to Approbation as a ‘Fatwa’ tool to discuss and treat the reality of the Muslim minorities away from arbitrariness and fancy. In the respect, I referred to the descriptive framework that is based mainly on analysis along with backing to the deductive and rational methods. The research exposes, in this context, the set of fundamentalists of Fiqh the minorities and handles the value of Approbation through studying the origin of its argument, its usage, the conditions of its consideration, and the organizational frame for its practice. All in all, according to this study Approbation is regarded as one of the most valuable proofs of Fiqh the minorities that meets the normative requirements within an organizational framework based on axes of integration, objectivity, legitimacy, and methodology. The prominence of Approbation as an evidence is manifested firstly on its enrichment of the research on Fiqh the minorities, secondly, on its modest dealing with their realities, and thirdly on ensuring the continuity of God’s will to content his creatures.
Keywords: الفقه الإسلامي -- الأقليات المسلمة -- المسائل الفقهية